Altered DNA Methylation of Long Noncoding RNA H19 in Calcific Aortic Valve Disease Promotes Mineralization by Silencing NOTCH1. Issue 23 (6th December 2016) - Hadji, Fayez; Boulanger, Marie-Chloé; Guay, Simon-Pierre; Gaudreault, Nathalie; Amellah, Soumiya; Mkannez, Guada; Bouchareb, Rihab; Marchand, Joël Tremblay; Nsaibia, Mohamed Jalloul; Guauque-Olarte, Sandra; Pibarot, Philippe; Bouchard, Luigi; et al.
Abstract : Background: Calcific aortic valve disease is characterized by an abnormal mineralization of the aortic valve. Osteogenic activity in the aortic valve is under the control of NOTCH1, which regulates the expression of key pro-osteogenic genes such as RUNX2 and BMP2 . Long noncoding RNAs (lncRNAs) may reprogram cells by altering the gene expression pattern. Methods: Multidimensional genomic profiling was performed in human aortic valves to document the expression of lncRNAs and the DNA methylation pattern in calcific aortic valve disease. In-depth functional assays were carried out to document the impact of lncRNA on the mineralization of the aortic valve. Results: We documented that lncRNA H19 (H19 ) was increased in calcific aortic valve disease. Hypomethylation of the promoter region was observed in mineralized aortic valves and was inversely associated with H19 expression. Knockdown and overexpression experiments showed that H19 induces a strong osteogenic phenotype by altering the NOTCH1 pathway. Gene promoter analyses showed that H19 silenced NOTCH1 by preventing the recruitment of p53 to its promoter. A knockdown of H19 in valve interstitial cells (VICs) increased the expression of NOTCH1 and decreased the level of RUNX2 and BMP2, 2 downstream targets repressed by NOTCH1 . In rescue experiments, the transfection of a vector encoding for the active Notch intracellular domain prevented H19 -induced mineralization of valve interstitial cells. Conclusions: These findings indicate that a dysregulation of DNA methylation in the promoter of H19 during calcific aortic valve disease is associated with a higher expression of this lncRNA, which promotes an osteogenic program by interfering with the expression of NOTCH1. Abstract : Supplemental Digital Content is available in the text.